Актуальні питання юридичної науки та практики. Вип. 2 - Хмельницький інститут ПрАТ «ВНЗ «МАУП» (My University, 2022)
У збірнику наукових праць вміщено статті за матеріалами інтернет-конференції студентів та молодих вчених "Актуальні питання юридичної науки та практики". Авторами статей розкрито такі питання: трудові права на період воєнного стану; ознаки економічної копурції в Україні; правовий статус господарських товариств як суб’єктів господарювання; інструменти примирення сторін в цивільному судочинстві; шляхи вдосконалення законодавства України та проблеми його адаптації до правової системи Євросоюзу тощо. The collection of scientific works contains articles based on the materials of the Internet conference of students and young scientists "Current Issues of Legal Science and Practice". The authors of the articles have revealed the following issues: labor rights during the period of martial law; signs of economic corruption in Ukraine; legal status of business entities as business entities; instruments for conciliation of parties in civil proceedings; ways to improve the legislation of Ukraine and the problems of its adaptation to the legal system of the European Union, etc.